Making the most of maps: GIS and topographical survey on the Island of Jarak - Fauzi, Rosmadi; Hussin, Azhar; A. Ghani, Azman; Ismail, Khaira (Malaysian Journal of Science, 2008)
The purpose of the GIS and topographic survey was to gather survey data on the natural, topographical and geological features of the island of Jarak, as well as its elevations. The topographic survey in this expedition fundamentally involved the production of maps and plans which were true to scale in the study area. The developed topographic maps will accurately represented details of both the natural and built environment on the island. Elevations data were taken with surveying equipment at several points on the island and plotted using GIS software. Through GIS analysis and field verification techniques, the dominant, natural and topographic features of the island have been identified and mapped.